A multicarrier QAM modulator for WCDMA base-station with on-chip D - Kosunen, M. (IEEE Transactions on VLSI systems)
In this paper, design and implementation of a multicarrier quadrature amplitude modulation (QAM) modulator for a wideband code division multiple access (WCDMA) base-station with a 14-bit on-chip D/A converter is described. The modulator is capable of modulating four carriers with four independent in phase (I) and quadrature (Q) data streams. The proposed modulator structure consists of an interpolation chain for data streams and four digital frequency synthesizer/modulators, which are based on a coordinate rotation digital computer (CORDIC) vector rotation algorithm. The interpolation chain consists of a root-raised cosine pulse shaping filter and three half-band filters for image filtering. The modulated carriers are combined to form a multicarrier WCDMA signal. The SINC-attenuation effect of a digital/analog (D/A) converter is canceled by an inverse-SINC predistortion filter. The multicarrier signal is converted to the analog domain with a 14-bit current steering D/A converter, which is integrated on the same silicon chip. The modulator is implemented with a 0.35-mum BiCMOS process with CMOS transistors only